2016
DOI: 10.1177/0272989x16671925
|View full text |Cite
|
Sign up to set email alerts
|

Reliability, Validity, and Feasibility of Direct Elicitation of Children’s Preferences for Health States

Abstract: The few studies found through this systematic review demonstrate that there is little empirical evidence on which to judge the use of direct preference elicitation methods with children regarding health states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…This existing research comparing adult and adolescent preferences was conducted using the CHU-9D instrument and it is unknown whether this result is also valid for other child instruments such as the EQ-5D Youth version (EQ-5D-Y). The feasibility and validity of adolescent preferences is largely unknown, as is the impact of adolescent, adult proxy (adults imagining a child) and adult study perspectives on the preferences obtained for other child instruments [15,16]. It is clear that the choice of values has important implications for utility estimation and resulting policy and practice decisions [12].…”
Section: Survey Design and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This existing research comparing adult and adolescent preferences was conducted using the CHU-9D instrument and it is unknown whether this result is also valid for other child instruments such as the EQ-5D Youth version (EQ-5D-Y). The feasibility and validity of adolescent preferences is largely unknown, as is the impact of adolescent, adult proxy (adults imagining a child) and adult study perspectives on the preferences obtained for other child instruments [15,16]. It is clear that the choice of values has important implications for utility estimation and resulting policy and practice decisions [12].…”
Section: Survey Design and Data Collectionmentioning
confidence: 99%
“…In addition, we know little about how current preference elicitation methods work for children. There are concerns regarding the validity of directly eliciting adolescent preferences, and the age at which children can reliably complete valuation tasks [16]. However, previous research on the CHU-9D instrument has reported that children aged 11-17 years can complete BWS tasks [11].…”
Section: Introductionmentioning
confidence: 99%
“…The arguments that the taxpayer perspective should be adopted and that completing a valuation task requires abstract thinking both speak in favour of a general population sample [2,[5][6][7]. However, evidence also shows that preferences of children and adolescents themselves can be assessed, and that they place different weights on impairments than adults [8][9][10][11][12][13][14]. Apart from the question of who should provide the values there is the question of which valuation task is most appropriate to use.…”
Section: Introductionmentioning
confidence: 99%
“…Before doing so, however, we need to establish the feasibility of recruiting adolescent participants and the appropriate elicitation methods for measuring health state preferences from this population. A recent systematic review of studies that directly measured preferences in adolescents observed that only 26 out of 74 studies in the past 25 years have reported some form of feasibility, reliability, or validity for commonly used elicitation methods [ 19 ]. To move the field forward, there is a need to better understand how these elicitation methods work with adolescents.…”
Section: Introductionmentioning
confidence: 99%